Histopathological characterization of nephritides in the brown capuchin monkey, Cebus apella (Primates: Cebidae) - Juan T. Borda; Vanessa Nunes-Bastos; Silvia Pérez-Escalá; Marcial Sánchez-Negrette (Revista de Biología Tropical, 2000)
The renal lesions are of special importance in the captive primates. The most commonly pathologies are: pyelonephritis, nephrocalcinosis, glomerulonephritis, congenital malformations, hydronephrosis and functional diseases. We report the histopathological study of renal lesions of five cases of deaths in Cebus apella (Primates) of the Argentinean Primate Center. The ages of the monkeys were from 4 months to 15 years old. Microscopically, we have observed principally acute diffuse proliferative glomerulonephritis, hilar mesangio proliferative glomerulonephritis, extracapilar glomerulonephritis with crescents, chronic interstitial nephritis and chronic pyelophritis.